Public Relations Communication Strategy of Bawaslu Mandailing Natal In Managing Instagram Media In The 2024 Election - Futra, Sandy; Farid, Ahmad Salman; Desiana, Desiana (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to determine the communication strategy of Bawaslu Mandailing Natal's public relations in managing Instagram media in the 2024 election and the obstacles to Bawaslu's public relations communication strategy in managing Instagram media in the 2024 election. This research was conducted at the Bawaslu Mandailing Natal Office. The research method used is a qualitative research method with the type of Field Research . The data analysis technique used is by conducting observations, interviews and documentation to obtain the desired data. The results of this study explain that the communication strategy carried out by Bawaslu Mandailing Natal is to encourage the distribution of information on Bawaslu Mandailing Natal's social media and encourage the official Bawaslu Instagram social media account. In addition, the next Bawaslu Mandailing Natal public relations communication strategy is to increase content in the form of Bawaslu activities and posts regarding election regulations which will later be distributed by Bawaslu Mandailing Natal Public Relations by managing or using the official Bawaslu Mandailing Natal social media account, namely: @bawaslu_madina. Social media management, especially Instagram, is very important for the success of an agency that will later be easier to achieve the desired goals. The management of Bawaslu Mandailing Natal's Instagram media is still experiencing obstacles due to limited Human Resources (HR) where it can be seen that the ability of the Staff to create creative content is still lacking and there are obstacles in the infrastructure experienced by the Public Relations of Bawaslu Mandailing Natal so that it is very difficult to create creative content.